2017
DOI: 10.18203/issn.2454-5929.ijohns20170612
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of surgical outcomes of septorhinoplasty patients: a clinical study

Abstract: <p class="abstract"><strong>Background:</strong> Septorhinoplasty is commonly done procedure in ENT basic setup. It is done to relieve nasal obstruction and also to give better cosmetic appearance. There is dictum in nasal anatomy, 'as goes septum, goes nasal tip. It is clearly known that septum deviations change the cosmetic appearance of persons. <span lang="EN-IN"> Present study had done to access pre and post-operative satisfaction of patients with use of rhinoplasty outcome questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…These problems may negatively affect the life of the patients and result in a decrease in the QoL (Taylan et al, 2021). In studies evaluating the quality of life in septorhinoplasty patients, it has been reported that the preoperative quality of life of the patients is significantly lower (Bulut et al, 2017;Chavan et al, 2017;Oppermann et al, 2022;Wähmann et al, 2018;Zojaji et al, 2018). In our study, it was determined that the QoL of the patients was low according to the preoperative ROE score and that there was a weak and negative statistically significant correlation between the preoperative NOSE and ROE scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems may negatively affect the life of the patients and result in a decrease in the QoL (Taylan et al, 2021). In studies evaluating the quality of life in septorhinoplasty patients, it has been reported that the preoperative quality of life of the patients is significantly lower (Bulut et al, 2017;Chavan et al, 2017;Oppermann et al, 2022;Wähmann et al, 2018;Zojaji et al, 2018). In our study, it was determined that the QoL of the patients was low according to the preoperative ROE score and that there was a weak and negative statistically significant correlation between the preoperative NOSE and ROE scores.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the symptoms and QoL of patients after surgery using measurement tools specific to the disease is important in preventing possible complications and increasing patient satisfaction, QoL, and comfort (Çelik and Altıntaş;Gerecci et al, 2019;Oppermann et al, 2022;Wähmann et al, 2018;Zojaji et al, 2018). There are studies evaluating the effects of septorhinoplasty on quality of life (Bulut et al, 2017;Chavan et al, 2017;Oppermann et al, 2022;Wähmann et al, 2018;Zojaji et al, 2018) and nasal obstruction (Oppermann et al, 2022;Taylan et al, 2021) and comfort (Taylan et al, 2021). However, no study was detected that simultaneously evaluates the effects of septorhinoplasty on quality of life, nasal obstruction, and comfort with measurements pre-and postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study are comparable with a recent study conducted by Chavan and coworkers (2017) who also reported that most of the patients (55.0%) were males and 45.0% were females. [2] During the period of young age, people are more concerned about their appearance and want to look more attractive. It is important to mention that significant majority (65.0%) of patients was 18-25 years old while 35.0% patients were 26-30 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Open septorhinoplasty is an important cosmetic surgery done by otorhinolaryngologists. [2] Nasal obstruction is a most frequent dilemma in the otolaryngology practice which can occur due to various factors. [3] The causes of nasal obstruction are divided in two components namely fixed and dynamic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation